Bài 2: Phương trình lượng giác cơ bản

trần nguyễn mai linh

tìm x khi Cosx + cos(\(\frac{\Pi}{6}\) + 2x) =0

Nguyễn Việt Lâm
17 tháng 9 2020 lúc 21:18

\(\Leftrightarrow cos\left(2x+\frac{\pi}{6}\right)=-cosx\)

\(\Leftrightarrow cos\left(2x+\frac{\pi}{6}\right)=cos\left(\pi-x\right)\)

\(\Leftrightarrow\left[{}\begin{matrix}2x+\frac{\pi}{6}=\pi-x+k2\pi\\2x+\frac{\pi}{6}=x-\pi+k2\pi\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{5\pi}{18}+\frac{k2\pi}{3}\\x=-\frac{7\pi}{6}+k2\pi\end{matrix}\right.\)


Các câu hỏi tương tự
Phuong Tran
Xem chi tiết
Nguyễn Kiều Anh
Xem chi tiết
Julian Edward
Xem chi tiết
Anh Trâm
Xem chi tiết
Nguyễn Kiều Anh
Xem chi tiết
Nguyễn Kiều Anh
Xem chi tiết
Ânn Thiênn
Xem chi tiết
lâm khánh đại
Xem chi tiết
Phạm Nhật Trúc
Xem chi tiết